2016
DOI: 10.1002/bem.21959
|View full text |Cite
|
Sign up to set email alerts
|

Microwave fields have little effect on α‐synuclein aggregation in a Caenorhabditis elegans model of Parkinson's disease

Abstract: Potential health effects of radiofrequency (RF) radiation from mobile phones arouse widespread public concern. RF fields from handheld devices near the brain might trigger or aggravate brain tumors or neurodegenerative diseases such as Parkinson's disease (PD). Aggregation of neural α-synuclein (S) is central to PD pathophysiology, and invertebrate models expressing human S have helped elucidate factors affecting the aggregation process. We have recently developed a transgenic strain of Caenorhabditis elegans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…C. elegans has also been widely used as PD models since it also shows increased levels of human α‐synuclein associated with PD. [ 16–18 ] In the previous report, DO was found to exhibit neuroprotective effects on the brains of rats by decreasing oxidative stress and inflammation. [ 19 ] In this study, we investigate the prevention of dopaminergic neuronal dysregulation in C. elegans using DO‐loaded zein‐CMC (DZC) complex.…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans has also been widely used as PD models since it also shows increased levels of human α‐synuclein associated with PD. [ 16–18 ] In the previous report, DO was found to exhibit neuroprotective effects on the brains of rats by decreasing oxidative stress and inflammation. [ 19 ] In this study, we investigate the prevention of dopaminergic neuronal dysregulation in C. elegans using DO‐loaded zein‐CMC (DZC) complex.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that α-syn tetramers have a small possibility to contribute to aggregates formation [53].the dramatic increase in toxic monomeric α-syn could greatly contribute to the increased levels of multimerization observed in our results following exposure. Although dePomerai [54] did not find any synuclein aggregation following two modes of exposure in the nematode C. elegans, we have to point out that this model system is largely resistant to Radiofrequency exposure as found by our own experimental data [55].…”
Section: A-syn Oligomerizationmentioning
confidence: 59%
“…These assays have further applications for inexpensive rapid examination and screening of PD treatments. 10 , 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“…These assays have further applications for inexpensive rapid examination and screening of PD treatments. 10,67,68 DA neurons are more vulnerable to oxidative stress in the 6-OHDA model because this compound generates reactive oxygen species, which are the primary regulators of neuronal apoptosis and death. In particular, 6-OHDA generates the superoxide radical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation